Materializing the international migrant health policy in health sciences curricula in Chile. - Álvarez-Cruces, Debbie; Nocetti-de-la-Barra, Alejandra; Mansilla-Sepúlveda, Juan (Revista Cuidarte)
Introduction: In Chile, the International Migrant Health Policy (PSMI in Spanish) mandates the inclusion of topics such as migration, interculturality, human rights, social determinants of health, and gender in higher education curricula. However, it is unknown whether this effectively happens. Objective: To understand the materialization of the PSMI in health sciences curricula. Materials and Methods: This interpretative/hermeneutic study included semi-structured interviews with program directors, academic faculty, clinical professors, and students. It also involved a document analysis across different health sciences degree programs at three regional universities in Chile. Data analysis included open, axial, and selective coding with ATLAS.ti version 24. Results: A total of 179 informants participated. Three main categories emerged: Health Institution Setting, University Institution Setting, and Degree Program Setting, each comprising facilitating or hindering subcategories for materializing policy materialization. The hermeneutic analysis made it possible to interrelate these subcategories, producing a semantic network to understand the phenomenon. Facilitators were scarce and isolated from the network core, while hindrances were more numerous, cohesive, and robust, reinforcing an ethnocentric model of professional education validated by ethnocentric healthcare practices in clinical settings. Discussion: The concept of "cultural blinders" is proposed in place of "cultural blindness" as there is awareness of the cultural influences on healthcare that are nonetheless not integrated. Conclusions: Current curricula do not align with the PSMI. Coordinated policies between the Ministry of Education and the Ministry of Health are imperative to reverse the existing healthcare status quo.